Genome-Wide Identification and Expression Profile of Dof Transcription Factor Gene Family in Pepper (Capsicum annuum L.) - Wu, Zhiming; Cheng, Jiaowen; Cui, Junjie; Xu, Xiaowan; Liang, Guansheng; Luo, Xirong; Chen, Xiaocui; Tang, Xiangqun; Hu, Kailin; Qin, Cheng (Frontiers in Plant Science, 2016)
Dof (DNA-binding One Zinc Finger) transcription factor family is unique to plants and has diverse roles associated with plant-specific phenomena, such as light responses, phytohormone and defense responses, and seed development and germination. Although genome-wide analysis of this family has been performed in many species, information regarding Dof genes in the pepper, Capsicum annuum L., is extremely limited. In this study, exhaustive searches of pepper genome revealed 33 potential CaDofs that were phylogenetically clustered into four subgroups. Twenty-nine of the 33 Dof genes could be mapped on 11 chromosomes, except for chromosome 7, at different densities. The intron/exon organizations and conserved motif compositions of these genes were also analyzed. Additionally, phylogenetic analysis and classiﬁcation of the Dof transcription factor family in eight plant species revealed that S. lycopersicum and C. annuum, and O. sativa and S. bicolor Dof proteins may have evolved conservatively. Moreover, comprehensive expression analysis of CaDofs using a RNA-seq atlas and quantitative real-time polymerase chain reaction (qRT-PCR) revealed that these genes exhibit a variety of expression patterns. Most of the CaDofs were expressed in at least one of the tissues tested, whereas several genes were identified as being highly responsive to heat and salt stresses. Overall, this study described the first genome-wide analysis of the pepper Dof family, and these genes exhibited different expression patterns in all primary fruit developmental stages and tissue types, and response to abiotic stress. In particular, some Dof genes might be used as biomarkers for heat and salt stress. The results could expand our understanding of the roles of Dof genes in pepper. Key words: Pepper; DNA-binding one zinc finger; Phylogenetic analysis; Expression analysis; Heat stress; Salinity stress